A Translation Analysis Of Noun Phrase In The Appeal Novel Into Naik Banding By Bhimasena - Monalisa, Lusiani, Dr. Dwi Haryanti, M.Hum, Nur Hidayat, S.Pd., M.Pd (2015)
This research aims at clasifying the translation variations of noun phrase in The Appeal novel into Naik Banding by Bhimasena and describing the translation accuracy of noun phrase found in the The Appeal novel into Naik Banding by Bhimasena. This research belongs to descriptive qualitative research. The data of this research are noun phrase and their translation. The data source containing of noun phrase in The Appeal novel into Naik Banding by Bhimasena. The writer uses documentation as the method of collecting data in this research. The results of the research show that, firstly there are 31 translation variation of noun phrase in The Appeal novel and its translation. There are 19 types of translation variations of English noun phrase are translated into Indonesian noun phrase, such as: 48 or 4,3% data of NP1 translated into NPa, NPb, NPe, NPl, and NPp, 71 or 6,4% data of NP2 translated into NPa, NPc, NPg, NPi, and NPn, 2 or 0,1% data of NP3 translated intoNPk, 37 or 3,3% data of NP5 translated into NPa, NPb, NPc, NPd and NPm, 2 or 0,1% data of NP6 translated into NPi, 4 or 0,3% data of NP8 translated into NPd and NPg. There are also 17 or 1,5% data of NP translated into verb phrase, 20 or 2,2% data of NP translated into adjective phrase, 40 or 3,6% data of NP translated into adverb phrase, 27 or 2,4% data of NP translated into prepositional phrase, 169 or 15,2% data of NP translated into noun, 22 or 1,9% data of NP translated into verb, 24 or 2,1% data of NP translated into adjective, 11 or 0,9% data of NP translated into adverb, 11 or 0,9% data of NP translated into numeral, 1 or 0,09% data of NP translated into pronoun, 350 or 31,6% data of NP translated into clause, 15 or 1,3% data of NP translated into sentence, and 39 or 3,5% data of deletion of noun phrase. Secondly, in the accuracy of translation classified into three, namely; accurate, less accurate, and inaccurate. The writer found 456 or 68,3% data of accurate, 158 or 23,6% data of less accurate, and 53 or 7,9% data of inaccurate. Here means that the variations on translation do not significantly affect the accuracy.